1983
DOI: 10.1152/ajpregu.1983.245.3.r334
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic regulation of body mass, food intake, and reproduction in meadow voles

Abstract: Adult male voles were maintained for 10 wk in long or short photoperiods (14 or 10 h of light/day). A third group of animals housed in the long photoperiod was implanted with capsules containing melatonin. Body weight and food intake were measured weekly; various tissues were weighed and analyzed at the time of autopsy. After 10 wk, voles in the short photoperiod weighed 20% less and consumed 30% less food than those housed in the long photoperiod. Total body water and lean body mass were reduced in the short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…Note an increase in apoptotic cells (arrows) and reduction in seminiferous epithelium in the testes after 4 (b) and 8 (c) weeks. Also, see Table 3 Several studies revealed that seasonal changes in body and organ weights of bank voles and other small mammals remain under control of the photoperiod (Dark et al 1983;Bartness et al 2002;Peacock et al 2004;WƂostowski et al 2004;KrĂłl et al 2005). It is reasonable to conclude that the effect of photoperiod on myocyte and hepatocyte cell size is also mediated through the short-photoperiod mediator melatonin (Bartness et al 2002;WƂostowski et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note an increase in apoptotic cells (arrows) and reduction in seminiferous epithelium in the testes after 4 (b) and 8 (c) weeks. Also, see Table 3 Several studies revealed that seasonal changes in body and organ weights of bank voles and other small mammals remain under control of the photoperiod (Dark et al 1983;Bartness et al 2002;Peacock et al 2004;WƂostowski et al 2004;KrĂłl et al 2005). It is reasonable to conclude that the effect of photoperiod on myocyte and hepatocyte cell size is also mediated through the short-photoperiod mediator melatonin (Bartness et al 2002;WƂostowski et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal changes in body mass of bank voles and other small mammals from the temperate zone are under control of photoperiod (Dark et al 1983; Bartness et al 2002;Bonda-Ostaszewska et al 2012), and in some species, the changes in white and brown adipose tissues are thought to contribute significantly to the changes in body weight (Bartness et al 2002). However, the bank voles belong to those species which exhibit no seasonal changes in fat mass (Klaus et al 1988;Bonda-Ostaszewska et al 2012), and the changes in weight of other organs such as liver, kidneys, and testes contribute only slightly (about 10 %) to the changes of body weight (WƂostowski et al 1988(WƂostowski et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Iverson and Turner, 1974;Hansson, 1992;Aars and Ims, 2002). This reduction affects all three major carcass components -lean tissue, fat and body water (Dark et al, 1983). A similar strategy is also adopted by immature voles born late in the season, which delay growth to the adult size until the next spring (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…When the nocturnal part of the circadian sleepwake cycle in humans is truncated, inappropriate overeating during extended wakeful periods ensues contributing to obesity and associated health risk factors [44,45] . Similarly, a seasonal change in the length of circadian exposure to light produces changes in feeding and body fat accumulation in some mammals [46] . Additional evidence for a functional interaction between the circadian clock and the ANS energy regulatory circuits involves loss of feeding, locomotor, and thermogenic periodicities when either the ANS or SCN circuits are disrupted.…”
Section: The Central Clock Coordinates Ans Control Of Feedingmentioning
confidence: 99%